Fundamentals of microbiome science : how microbes shape animal biology - Douglas, A. E. 1956- (Princeton University Press, 2018)
"This book provides an accessible and authoritative guide to the fundamental principles of microbiome science, an exciting and fast-emerging new discipline that is reshaping many aspects of the life sciences. Resident microbes in healthy animals--including humans-can dictate many traits of the animal host. This animal microbiome is a second immune system conferring protection against pathogens; it can structure host metabolism in animals as diverse as reef corals and hibernating mammals; and it may influence animal behavior, from social recognition to emotional states. These microbial partners can also drive ecologically important traits, from thermal tolerance to diet, and have contributed to animal diversification over long evolutionary timescales. Drawing on concepts and data across a broad range of disciplines and systems, Angela Douglas provides a conceptual framework for understanding these animal-microbe interactions while shedding critical light on the scientific challenges that lie ahead. Douglas explains why microbiome science demands creative and interdisciplinary thinking-the capacity to combine microbiology with animal physiology, ecological theory with immunology, and evolutionary perspectives with metabolic science. An essential introduction to a cutting-edge field that is revolutionizing the life sciences, this book explains why microbiome science presents a more complete picture of the biology of humans and other animals, and how it can deliver novel therapies for many medical conditions and new strategies for pest control."- Resumé vydavatel